Magnetic and Phase Behavior of Magnetic Water‐in‐Oil Microemulsions. Issue 4 (22nd April 2017) - Brown, Paul; Mohamed, Azmi; Ardyani, Tretya; Rogers, Sarah E.; Eastoe, Julian
Abstract: Magnetic water‐in‐oil microemulsions with anisotropic morphology have been generated by mixing single‐chain magnetic surfactants (dodecyltrimethylammonium trichloromonobromoferrate, DTAF) with non‐magnetic di‐chain analogues (didodecyldimethylammonium bromide, DDAB). Full phase diagrams have been mapped as a function of surfactant composition, water content, and temperature. It was shown that for all surfactant concentrations [Surfactanttotal ], on replacing 30 wt% DDAB with DTAF optimum (i.e. wt% of the total surfactant) w ratios ( w = [water]/[surfactant]) could be achieved; up to w = 120 for [Surfactanttotal ] = 0.050 M. Small‐angle neutron scattering (SANS) indicated that microemulsion droplets have a rod‐like morphology with a radius commensurate with the surfactant tail length and an aspect ratio between 6 and 35. In the presence of a large magnetic field (6.7 T) no reorientation of the droplets was observed by SANS.